30.5k views
24 votes
Pls answe asap and show work!

11. What is (f.g)(x)?
f(x) = x3 + 3
g(x) = 2x2 + x - 1
-
=

Pls answe asap and show work! 11. What is (f.g)(x)? f(x) = x3 + 3 g(x) = 2x2 + x - 1 - =-example-1

2 Answers

4 votes
  • (fg)(x)
  • f(x).g(x)
  • (x³+3)(2x²+x-1)
  • x³(2x²+x-1)+3(2x²+x-1)
  • 2x⁵+x⁴-x³+6x²+3x-3

User Sandeep Vokkareni
by
4.8k points
1 vote

Answer:


(f \cdot g)(x)=2x^5+x^4-x^3+6x^2+3x-3

Explanation:

Given functions:


f(x)=x^3+3


g(x)=2x^2+x-1

Therefore:


\begin{aligned}(f \cdot g)(x) & =f(x) \cdot g(x)\\& = (x^3+3)(2x^2+x-1)\\& = x^3(2x^2)+x^3(x)+x^3(-1)+3(2x^2)+3(x)+3(-1)\\& = 2x^5+x^4-x^3+6x^2+3x-3\end{aligned}

User Jenessa
by
4.9k points